Body composition, energy availability, training, and menstrual status in female runners - Ihalainen, J. K.; Kettunen, O.; McGawley, K.; Solli, G. S.; Hackney, A. C.; Mero, A. A.; Kyröläinen, H. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To determine body composition, energy availability, training load, and menstrual status in young elite endurance running athletes (ATH) over 1 year, and in a secondary analysis, to investigate how these factors differ between nonrunning controls (CON), and amenorrheic (AME) and eumenorrheic (EUM) ATH. Correlations to injury, illness, and performance were also examined.